A potential gene delivery strategy using BK virus. Issue 2 (3rd April 2019) - Husseiny, Mohamed I.; Soliman, Sameh
Abstract: Recombinant BK virus (rBKV) is able to express polypeptides under control of its native BKV late promoter. This ability helps to use this construct as a good reporter since it can infect human cells. In this study, we generate a BKV construct containing Renilla luciferase ( Rluc ) sequences under control of the BKV late promoter. The activity of Rluc was strongly detected in Vero-76 and Cos-1 cells transfected with rBKV-Rluc-myc-2A-VP2 construct, indicating the production of a functional enzyme driven by the native late promoter. Furthermore, a construct made of rBKV-IL2SP-Rluc-myc-2A-VP2 by introducing human IL2 secretion peptide (IL2 SP) caused secretion of IL2SP-Rluc-myc into the culture medium. As a concluding remark, a potential infectious rBKV that can express foreign antigens such as Rluc was generated successfully. The proposed strategy would be useful to engineer recombinant forms of rBKV with many potential applications including development of antiviral assay for new drugs, human vaccines and gene delivery systems for immunotherapeutic or cell transduction.